Predictors of Appropriate Antibiotic Use in Bacteremia Patients Presenting at the Emergency Department - Pariwat Phungoen; Areerat Kraisriwattana; Korakot Apiratwarakul; Lumyai Wonglakorn; Kittisak Sawanyawisuth (MDPI AG, 2019)
Sepsis is a condition that requires appropriate antibiotic treatment at the emergency department (ED). Most previous studies conducted on inappropriate antibiotic use at the ED were conducted in developed countries with a low percentage of sepsis. This study aimed to find additional clinical predictors for appropriate antibiotic use in bacteremia patients presenting at the ED from a developing country, in which there is a higher proportion of patients with sepsis. We included adult patients who presented at the ED with clinical suspicion of infection and bacteremia. Patients allocated to the appropriate antibiotic group were those in whom the prescribed antibiotic was sensitive to the pathogen. Predictors and outcomes of appropriate antibiotic use were analyzed. A total of 3133 patients who met the study criteria presented at the ED during the study period. Of those, 271 patients were diagnosed with bacteremia, 48 of whom (17.71%) received inappropriate antibiotic prescriptions. Only pulse rate was an independent factor for appropriate antibiotic treatment, with an adjusted odds ratio of 1.019 (95% CI of 1.001, 1.036). In terms of clinical outcomes, the inappropriate antibiotic group had higher proportions of 28-day mortality (29.17% vs. 25.25%; p-value = 0.022) and longer hospitalization (14 vs. 9 days; p-value = 0.003). This study found that inappropriate antibiotics were prescribed in 17% of bacteremia patients presenting at the ED and that high pulse rate was an indicator for appropriate antibiotic prescription. Patients with inappropriate antibiotic administration had longer hospitalization and higher 28-day mortality than those who received appropriate antibiotic treatment.